Battlestar Galactica. Season 2.5 [videorecording (DVD)] - Rymer, Michael, 1963-; Olmos, Edward James; McDonnell, Mary; Sackhoff, Katee; Bamber, Jamie, 1973-; Callis, James; Helfer, Tricia; Beckel, Graham, 1949-; Bennett, Matthew, 1954-; Stockwell, Dean, 1938-; Olmos, Bodie, 1975- (Universal Studios Home Entertainment, 2006)
Continuation of the epic, follows the ongoing battle of President Laura Roslin and Commander William Adama in their heart-pounding crusade to save humanity from the deadly robot Cylons.